Pengaruh modal kerja, total asset turnover dan harga gas alam dunia terhadap laba Perusahaan Gas Negara - Qailas Rafida; Yahya, M.; Midesia, Shelly (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
This study aims to determine the effect of working capital, Total Asset Turnover and world natural gas prices simultaneously on the profits of PT Perusahaan Gas Negara Tbk for the 2017-2022 period. The method used is a quantitative approach. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange and the website of Trading Economics. The data used is in the form of a quarterly period from 2017 to 2022 which was published for 6 consecutive years. Methods of data analysis using multiple linear regression. The results of the t-test research show that the independent variable working capital has no effect on the profits of PT Perusahaan Gas Negara Tbk for the 2017-2022 period. Total Asset Turnover has a positive and significant effect on the profits of PT Perusahaan Gas Negara Tbk for the 2017-2022 period. World natural gas prices have had a positive and significant effect on the profits of PT Perusahaan Gas Negara Tbk for the 2017-2022 period. The results of the F test study indicate that there is a jointly positive and significant influence between the working capital variable, Total Asset Turnover and world natural gas prices on the profits of PT Perusahaan Gas Negara Tbk for the 2017-2022 period with an Fcount value of 20.717 > Ftable 3.13. Based on the analysis of the coefficient of determination, the adjusted R2 value is 0.729, which means that 72.9% of the variation in the profit value of PT Perusahaan Gas Negara Tbk is determined by three influential variables, namely working capital, Total Asset Turnover and world natural gas prices.